2014
DOI: 10.4049/jimmunol.1400411
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor ABF-1 Suppresses Plasma Cell Differentiation but Facilitates Memory B Cell Formation

Abstract: Ag-primed B cells that result from an immune response can form either memory B cells or Ab-secreting plasma cells; however, the molecular machinery that controls this cellular fate is poorly understood. In this study, we show that activated B cell factor-1 (ABF-1), which encodes a basic helix-loop-helix transcriptional repressor, participates in this regulation. ABF-1 was prevalently expressed in purified memory B cells and induced by T follicular helper cell–mediated signals. ABF-1 expression declined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Four weeks after primary immunization, mice were injected with 100 μg NP 32 -KLH for the secondary immunization. In one experiment, bone marrow cells (1 × 10 6 cells) isolated from Ctrl and Cγ1-KO mice at 4 weeks after the secondary immunization with NP-KLH were subjected to ELISPOT analysis to test the number of NP-specific IgG-secreting plasma cells as follows 44 : B cells were seeded into a 96-well plate and incubated on nitrocellulose membranes (Bio-Rad), which was coated with NP 32 -BSA (100 μg ml −1 , Biosearch technologies), at 37 °C for 2.5 h. Attached cells were lysed by PBS-EDTA for 15 min, followed by two washes with 0.1% Tween 20 in PBS and one wash in PBS. The membrane was incubated at room temperature for 30 min with PBS and 1% bovine serum albumin (BSA), followed by incubation with anti-mouse IgG (Southern Biotechnology) at a dilution of 1000 × in PBS plus 1% BSA at room temperature for 1 h. NP-specific IgG-secreting cells were then visualized by the addition of enzyme substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Four weeks after primary immunization, mice were injected with 100 μg NP 32 -KLH for the secondary immunization. In one experiment, bone marrow cells (1 × 10 6 cells) isolated from Ctrl and Cγ1-KO mice at 4 weeks after the secondary immunization with NP-KLH were subjected to ELISPOT analysis to test the number of NP-specific IgG-secreting plasma cells as follows 44 : B cells were seeded into a 96-well plate and incubated on nitrocellulose membranes (Bio-Rad), which was coated with NP 32 -BSA (100 μg ml −1 , Biosearch technologies), at 37 °C for 2.5 h. Attached cells were lysed by PBS-EDTA for 15 min, followed by two washes with 0.1% Tween 20 in PBS and one wash in PBS. The membrane was incubated at room temperature for 30 min with PBS and 1% bovine serum albumin (BSA), followed by incubation with anti-mouse IgG (Southern Biotechnology) at a dilution of 1000 × in PBS plus 1% BSA at room temperature for 1 h. NP-specific IgG-secreting cells were then visualized by the addition of enzyme substrate.…”
Section: Methodsmentioning
confidence: 99%
“…In maturing B cells, E2A as well as E2-2 continue their activities to promote plasma cell differentiation, whereas the HLH protein ABF1 instructs germinal center cells to adopt the memory B-cell fate (Fig. 5;Massari et al 1998;Chiu et al 2014;Gloury et al 2016;Wöhner et al 2016). Finally, two additional HLH proteins-Bhlhe40 (Dec2) and Bhlhe41 (Dec1)-orchestrate the selfrenewal activity and development of B1 cells (Fig.…”
Section: Hlh Proteins and B-cell Diversitymentioning
confidence: 99%
“…Prdm1 is a downstream target of IRF4, and BLIMP1 can further increase the level of IRF4, thus reinforcing the plasma cell differentiation program in a feed forward loop ( 26 , 79 ). Morever, BLIMP1 represses the expression of Aicda ( 79 ) and Abf-1 ( 80 ).…”
Section: Transcription Factors Regulating Gc Formationmentioning
confidence: 99%
“…Activated B cell Factor 1 (ABF-1), a helix-loop-helix TF predominantly expressed in memory B cells, blocks the plasma cell differentiation program ( 80 ). An inducible ABF-1-ER mouse model demonstrated that induction of ABF-1 promotes GC formation and memory B cell differentiation ( 80 , 97 ). ZBTB32 and KLF2 are two factors expressed in memory B cells and which inhibit the GC response ( 98 ).…”
Section: Transcription Factors Regulating Gc Formationmentioning
confidence: 99%